Varied Composition and Underlying Mechanisms of Gut Microbiome in Neuroinflammation - Rai Khalid Farooq; Widyan Alamoudi; Amani Alhibshi; Suriya Rehman; Ashish Ranjan Sharma; Fuad A. Abdulla (Microorganisms, 2022)
The human gut microbiome has been implicated in a host of bodily functions and their regulation, including brain development and cognition. Neuroinflammation is a relatively newer piece of the puzzle and is implicated in the pathogenesis of many neurological disorders. The microbiome of the gut may alter the inflammatory signaling inside the brain through the secretion of short-chain fatty acids, controlling the availability of amino acid tryptophan and altering vagal activation. Studies in Korea and elsewhere highlight a strong link between microbiome dynamics and neurocognitive states, including personality. For these reasons, re-establishing microbial flora of the gut looks critical for keeping neuroinflammation from putting the whole system aflame through probiotics and allotransplantation of the fecal microbiome. However, the numerosity of the microbiome remains a challenge. For this purpose, it is suggested that wherever possible, a fecal microbial auto-transplant may prove more effective. This review summarizes the current knowledge about the role of the microbiome in neuroinflammation and the various mechanism involved in this process. As an example, we have also discussed the autism spectrum disorder and the implication of neuroinflammation and microbiome in its pathogenesis.